(untitled) (Research, Society and Development, 2024)
Objective: The aim of this study is to assess the neuropsychomotor development of children treated at the School Physiotherapy Clinic of the State University of Paraíba, through the application of the Alberta Infant Motor Scale (AIMS). Methods: This is a case series of a descriptive nature, employing a quantitative and cross-sectional approach, conducted at a School Physiotherapy Clinic. The sample consists of children without a clinical diagnosis, enrolled for physiotherapeutic care. The instruments used include a sociodemographic assessment form and the AIMS. This research was submitted to the Research Ethics Committee of UEPB and approved with the protocol number CAAE: 74237223.1.0000.5187. Results: Four children were included in the study, all born by cesarean section, two full-term and two preterm, with one being extremely preterm and the other late preterm. All mothers reported having received adequate prenatal care, and their pregnancies were desired, albeit unplanned. Three children exhibited complaints of sleep disturbances. Regarding the assessment of neuropsychomotor development, two were characterized as having atypical development, and two as having suspicious development. Conclusion: The children included in the study, despite the absence of any clinical diagnosis, demonstrated deficits in neuropsychomotor development. The use of AIMS proved to be significant not only for professionals, enabling them to plan appropriate interventions based on the results but also for parents and caregivers, contributing to enhancing child development in the home environment.